Synthesis and self-assembly behavior of multi-arm star amphiphilic polyelectrolyte systems and their applications in the delivery of biomolecules - He, Elaine Weiguo (2009)
Amphiphilic polyelectrolytes have attracted increasing attention due to their potential applications in the field of pharmaceutical science and biotechnology. The biocompatible polymers can self-assemble into nano-scale micelles, which provide similar structure and function as natural carriers. Biocompatibility, size and morphologies of the vehicles are important considerations in the design of suitable delivery systems, where they can be accomplished by manipulating block compositions, structure and lengths. Novel multi-arm star shape PEO was grafted with weak polybase or polyacid to produce stimuli-responsive amphiphilic polyelectrolytes. The three-dimensional branched structure offers greater proportion of end functional groups compared to linear structure of identical molecular weights, which induces greater solubility and more attractive aggregation behavior. The four-arm poly(ethylene oxide)-b-poly(2-(diethylamino)ethyl methacrylate) (PEO-b-PDEAEMA) and poly(ethylene oxide)-b-poly(methacrylic acid) (PEO-b-PMAA) block copolymers with tetrahedronal structure were successfully synthesized by the atom transfer radical polymerization technique to yield well-defined amphiphilic block copolymers of narrow polydispersity. The polymerization degree of four-arm PEO-b-PDEAEMA block copolymer was determined from the relative intensities of NMR spectra at 3.66 ppm (-CH2CH2O of the PEO block) and 4.02 ppm (-OCH2CH2N- of the PDEAEMA block), obtained a chemical structure of 4-arm PEO56-b-PDEAEMA74. The polymerization degree of the four-arm PEO-b-PtBMA copolymers was calculated from the peak intensity ratio of 3.58 ppm (-OCH2CH2O-) of PEO block and 1.40 ppm (-C(CH3)3) of tBMA block, to yield 4-arm PEO56-b-PtBMA88 block copolymer.